Assessment of rehabilitation potential in frail older people in the acute healthcare setting: a mixed methods study - Cowley, A. (2020)
Background Hospital admissions in frail older people are associated with a greater risk of disability, cognitive decline and adverse outcomes. Rehabilitation interventions are frequently cited as key in supporting frail older people’s recovery following periods of decompensation and ill health. Healthcare practitioners are required to make decisions, in the face of growing complexity of service provision, patient needs and expectations, about a patient’s potential to respond to rehabilitation interventions. The clinical currency in which these decisions are transacted is through the use of the term rehabilitation potential. Decisions about rehabilitation potential can determine what rehabilitation services a patient can access. There is no universally agreed, systematically assessed or explicitly operationalised model or clinical guideline that helps therapists to make consistent, transparent, patient-centred and evidence-based decisions about rehabilitation potential. This PhD study addresses this gap through the development of the Rehabilitation Potential Assessment Tool (RePAT) to be used with frail older people.